2015
DOI: 10.1542/peds.2014-2423
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Intravenous and Oral Pyridoxine Trial for Diagnosis of Pyridoxine-Dependent Epilepsy

Abstract: Pyridoxine-dependent epilepsy is a rare, autosomal recessive, treatable cause of neonatal seizures. Genetic testing can confirm mutations in the ALDH7A1 gene, which encodes antiquitin. To avoid delays in initiating treatment while awaiting confirmatory genetic testing, it is recommended that all neonates with unexplained seizures should receive trial of intravenous (IV) pyridoxine to assess for responsiveness. However, oral pyridoxine is not commonly continued in the absence of the typical EEG changes. Two cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Our search strategy yielded 497 patients with a confirmed genetic diagnosis of B6-dependent epilepsies. Of these, 90.7% (431/497) were diagnosed with the following three disorders: ALDH deficiency (69.4%), PNPO deficiency (13.2%), and PLPBP deficiency (9.2%) ( Figure 1 ) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Our search strategy yielded 497 patients with a confirmed genetic diagnosis of B6-dependent epilepsies. Of these, 90.7% (431/497) were diagnosed with the following three disorders: ALDH deficiency (69.4%), PNPO deficiency (13.2%), and PLPBP deficiency (9.2%) ( Figure 1 ) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , ...…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] This disease is characterized by an error in lysine catabolism as a result of a deficiency in alpha-aminoadipic semialdehyde (AASA) dehydrogenase otherwise known as antiquitin ( Figure). 2,7 Piperideine-6-carboxylate, which inactivates pyridoxal phosphate, subsequently accumulates. Pyridoxal phosphate is the activated form of pyridoxine and a cofactor for numerous reactions and enzymes.…”
Section: Pyridoxine-dependent Epilepsymentioning
confidence: 99%
“…6 Intravenous pyridoxine has a quick onset of action, though studies have shown that patients who appear to respond to IV pyridoxine by cessation of seizures after administration do not always have true PDE. 7 Often, it is given empirically with unknown etiology of neonatal seizures. Definitive diagnosis is through genetic testing.…”
Section: Pyridoxine-dependent Epilepsymentioning
confidence: 99%
See 2 more Smart Citations